Hierarchical prescribed-time ESO-based fault-tolerant controller synthesis for error-constrained coordination of networked robotic systems - Zhao, Xiaofeng; Wang, Zhuping; Zhang, Hao; Yan, Huaicheng (Nonlinear dynamics, 2025)
This paper investigates the prescribed-time coordination of networked robotic systems subject to complex unknowns including disturbances and actuator faults. A prescribed-time distributed estimator and extended state observer are proposed to acquire the leader’s information and complex unknowns, eliminating the need for prior knowledge of these unknowns and providing a promising approach for handling them within the prescribed time. To ensure the desired transient and steady-state responses, performance criteria are applied to coordination errors using a prescribed performance function. Subsequently, a hierarchical prescribed-time fault-tolerant control scheme is synthesized, consisting of a distributed estimator layer and a local control layer. The distinctive advantage of this hierarchical control scheme is that the coordination problem can be divided into two relatively simple sub-problems, namely coordination estimation and local robust tracking, easing control design and enhancing compatibility. Finally, simulation examples demonstrate the effectiveness of the theoretical results.